Profiles and drivers of antibiotic resistance genes distribution in one-stage and two-stage sludge anaerobic digestion based on microwave-H2O2 pretreatment. (October 2017) - Zhang, Junya; Liu, Jibao; Wang, Yawei; Yu, Dawei; Sui, Qianwen; Wang, Rui; Chen, Meixue; Tong, Juan; Wei, Yuansong
Graphical abstract: Highlights: Pretreatment with subsequent anaerobic digestion enhanced ARGs abundance reduction. Two-stage system showed some advantages over the ARGs abundance reduction. Anaerobic digestion was more effective on pathogens control than pretreatment. Changes of bacterial community was significantly correlated with ARGs profiles. Anaerobic digestion was a potential technology for ARGs control. Abstract: Three anaerobic digestion (AD) processes of waste activated sludge (WAS) were established including the control (mono-WAS), one-stage AD and two-stage AD along with microwave-H2 O2 pre-treatment (MW-H2 O2 ) to investigate the profiles and drivers of antibiotic resistance genes (ARGs) distribution concerning co-selection from heavy metals, intI1 and microbial community through qPCR and high-throughput sequencing method. Results showed that MW-H2 O2 could reduce the absolute gene copies of all ARGs while increased the relative abundance of most ARGs. After subsequent AD, both total ARGs quantities and relative abundance were enriched while two-stage AD showed some advantages over ARGs abundance reduction. Besides, AD was more effective on the potential pathogens reduction than MW-H2 O2 . AD could reduce the role of intI1 on the spread of ARGs, while mantel test and procrustes analysis indicated that the variation of ARGs abundance was closely associated with the discrepancy of bacterial community.